Kenya : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper on Poverty Reduction Strategy Papers (PRSPs) on Kenya explains macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major sources of financing. The overall objective of macroeconomic policy is to restore economic growth within a sustainable framework of low inflation and healthy balance of payments. The primary objective of the health sector reform process is to enhance accessibility and affordability of quality basic health services for all Kenyans with special emphasis on the poor and vulnerable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet